Books announced and noted (Quarterly Journal of Economics, 1897)
Journal Article Books announced and noted Get access The Quarterly Journal of Economics, Volume 11, Issue 4, July 1897, Pages 450–451, https://doi.org/10.1093/qje/11.4.450-a Published: 01 July 1897